Promising Educational Technologies for Professional Training - Sergeeva, Marina Georgiyevna (2020)
Comprehensive changes in Russian education are aimed at meeting the requirements of the modern economy and society. At the same time, the main vector in this area is the coordination of the content and component composition of professional training with the demands of the labor market and with the urgent need to increase the availability of high-quality educational services. Public experience demonstrates that objective reality makes significant adjustments to the professional training and education. Therefore, teachers should acknowledge and reflect in their professional activities all the new requirements presented by society in a timely manner. In the context of professional education, intensive search is carried out for adequate forms and methods to improve the effectiveness of education. In this regard, the practical value of simulation methods and technologies, aimed at revealing the creative potential of a future specialist, their individual and professional properties and the ability to function successfully in the new economic conditions, is increasing. Educational technologies as mechanisms for the joint activity of the teacher and students are aimed at the development of certain skills and abilities, as well as personal and professional development. The teacher should correctly apply educational technologies and methods to provide quality training for competent professionals. The variety of these methods is proposed to encourage intrinsic motivation, a lively interest of students in learning and self-development. The competencies of a qualified specialist and the criteria that he/she must meet have become the basis for creating a generalized concept of a professional. Along with the individual properties of the student, the foundation of the concept is knowledge and skills in the areas provided by the general and special components of the Federal State Educational Standards. In the framework of professional education, the main place in the educational process should be occupied by active educational technologies and methods, focused on intensifying the cognitive activities of students, supporting creative initiative and abilities and development of intellectual needs.